Republic of Latvia : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that since the last Article IV consultation discussions, economic activity in Latvia has maintained its momentum. GDP grew 7 1\2 percent in 2003 and 8 3/4 percent year over year in the first quarter of 2004; however, inflation climbed to 6.1 percent at end-June, from 3.6 percent at end-2003. Fiscal performance has improved appreciably, and public debt remains low. The general budget deficit, at 1.6 percent of GDP in 2003, narrowed by nearly 1 percentage point from 2002, reflecting lower-than-budgeted expenditures, unexpectedly high tax revenues, and lower net lending.